2019
DOI: 10.1016/j.nmd.2019.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric and neurodevelopmental aspects of Becker muscular dystrophy

Abstract: Little is known about the relationship between Becker Muscular Dystrophy (BMD) and mental disorders. This study aimed to clarify whether BMD is a risk factor for psychiatric diseases. We asked genetically or immunohistochemically confirmed BMD patients to participate in the study interview. Participants who consented to psychiatric tests underwent further assessments of intellectual, psychological, and neurodevelopmental disorders. In total, 76 (73%) of 105 BMD patients (median age, 37 years) completed the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 12 publications
1
29
1
Order By: Relevance
“…An important example of protocol burden was the amount of time that participation would cost patients or parents, needing to take time off from school or work. This was also underscored by a previous observational study in BMD patients that reported lack of time as main reason for non-participation [5]. The four studies at our institute mainly took place on week days, mostly outside of school hours.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…An important example of protocol burden was the amount of time that participation would cost patients or parents, needing to take time off from school or work. This was also underscored by a previous observational study in BMD patients that reported lack of time as main reason for non-participation [5]. The four studies at our institute mainly took place on week days, mostly outside of school hours.…”
Section: Discussionmentioning
confidence: 82%
“…These neuromuscular diseases form a spectrum in which DMD patients lose ambulation around their early teens, while BMD patients have a milder but more variable disease course [2,3]. In both diseases, a higher prevalence of learning and behavioral disabilities has been reported [4][5][6]. In DMD, this is associated with absence of different dystrophin isoforms in the brain [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of psychological disturbance in patients with NMD is well established across many conditions [113][114][115][116][117][118]. Given that mental health conditions are associated with poorer health outcomes [119], it is likely that they have an important impact on outcomes in NMD patients too.…”
Section: Psychological Supportmentioning
confidence: 99%
“… 1 In addition to skeletal muscle and heart pathology, patients with BMD may have neurodevelopmental-, behavioral comorbidities, learning disabilities and epilepsy. 1 , 4 7 For instance, autism features, inattention/hyperactivity features, language–speech delays and difficulties in reading, spelling and arithmetic are found in BMD. 1 , 4 , 6 , 7 It has been suggested that these comorbidities are related to a disturbed production of brain isoforms (i.e.…”
Section: Introductionmentioning
confidence: 99%